Complemented subspaces of p-adic second dual Banach spaces - Takemitsu Kiyosawa (International Journal of Mathematics and Mathematical Sciences)
Let K be a non-archimedean non-trivially valued complete field. In this paper we study Banach spaces over K. Some of main results are as follows: (1) The Banach space BC((l∞)1) has an orthocomplemented subspace linearly homeomorphic to c0. (2) The Banach space BC((c0)1) has an orthocomplemented subspace linearly homeomorphic to l∞.